2004
DOI: 10.1080/0897719042000201659
|View full text |Cite
|
Sign up to set email alerts
|

Functional Localization of Proprotein-convertase Furin and its Substrate TGFβ in EGF Receptor-expressing Gastric Chief Cells

Abstract: Furin, a proprotein-convertase, is distributed in the upper third layer and the lower quarter region of the rat gastric gland. We previously identified the upper furin-positive cells as parietal cells, and here, we identify the lower furin-positive cells as chief cells. Chief cells express three isoforms of transforming growth factor beta (TGFbeta), whose precursor requires cleavage by furin for its activation. When the chief cell mass was decreased in rats by adrenalectomy, pepsinogen-, furin-, and TGFbeta-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…We (39) have previously suggested that SPEM cells arise from the transdifferentiation of chief cells, based on the observation of cells expressing both intrinsic factor and SP/TFF2 at the bases of the fundic glands after a single dose of DMP-777 in gastrin-deficient mice. Although a previous investigation (36) has suggested that EGF receptors are enriched in human parietal cells, it is important to note that several investigators have reported that EGF receptors are enriched in rodent chief cells (19,26). Thus alterations in EGF receptor ligands might have particular influence on the differentiation and function of chief cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We (39) have previously suggested that SPEM cells arise from the transdifferentiation of chief cells, based on the observation of cells expressing both intrinsic factor and SP/TFF2 at the bases of the fundic glands after a single dose of DMP-777 in gastrin-deficient mice. Although a previous investigation (36) has suggested that EGF receptors are enriched in human parietal cells, it is important to note that several investigators have reported that EGF receptors are enriched in rodent chief cells (19,26). Thus alterations in EGF receptor ligands might have particular influence on the differentiation and function of chief cells.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, to examine the possible influence of SP/TFF2 as an autocrine growth factor of metaplasia, we studied lineage changes after DMP-777 administration in SP/TFF2-deficient mice. Additionally, previous investigations have noted that EGF receptors are strongly enriched in chief cells (19,26). Thus, given the important role of EGF receptor ligands in regulating epithelial mucosal cell differentiation (24), we also evaluated the role of the EGF receptor signaling pathway by treating waved-2 mice, which carry a point mutation that reduces tyrosine kinase activity in the EGF receptor (35).…”
mentioning
confidence: 99%
“…Another striking feature of the IL-11-treated fundus was the loss of chief cells; this was accompanied by reduced expression of active protease products of chief cells54 55; trypsin 4/10, amylase 2, pancreatic lipase-related protein 1 and furin, whereas pepsinogen C expression and localisation of the intrinsic factor were unchanged. It is unclear from the present study whether chief cell loss was secondary to a reduction in parietal cells, or whether IL-11 acts directly on the chief cell.…”
Section: Discussionmentioning
confidence: 99%
“…In the gastrointestinal tract, TGFβ isoforms regulate epithelial renewal through effects on cell proliferation [3][7], differentiation [8], [9], epithelial mesenchymal transition [10], [11], migration [12], and apoptosis [13]. TGFβ has been detected in human and murine milk [14], [15] and after suckling and oral administration, signaling is activated in gastric epithelial cells through receptors (TβRI and TβRII) and Smads central cascade [6], [15][17].…”
Section: Introductionmentioning
confidence: 99%